STUDY OF CLINICAL AND LABORATORY CHARACTERISTICS IN HUMAN TOXOCARIASIS AT MEDIC MEDICAL CENTER IN HO CHI MINH CITY, 2018 - 2019 (Vietnam Journal of Community Medicine, 2022)
Toxocariasis is a zoonotic helminthiasis caused by the migrating larvae of Toxocara canis and Toxocara cati, common roundworms of dogs and cats and becoming the problem of the public health. The clinical diagnosis of human toxocariasis is difficult because of the nonspecific clinical presentation, may lead to prolonged morbidity and development of health complications.Objectives: The study was conducted to describe clinical symptoms, laboratory changes in patients with Toxocara spp. infection.Methods: Cross-sectional descriptive study and analysis.Results: The mean age was 41 ± 15 years old, the age group 20 - < 60 years old accounted for 75.9%. The distribution of females was higher than that of males. The most common symptoms were in the skin (77.5%), followed by neurological manifestations (35.0%), digestive (31.7%) and respiratory manifestations (21.7%). All patients had an increase in the number of eosinophils in the peripheral blood, but 91.7% had a mild increase (from 500 - < 1,500 cells/mm3). The mean total serum IgE concentration was 764.7 ± 630.6 IU/mL, 43.3% of patients had an IgE increase less than 4 times the limit of normal (from 130 - < 520 IU/mL). The mean optical density of anti-Toxocara spp. IgG was 1.51 ± 0.85, the value distribution from 0.36 to 3.50.Conclusion: Clinical symptoms of human toxocariasis were diverse and manifest in many organs. The peripheral blood eosinophils, serum total IgE levels and anti-Toxocara spp. IgG were important laboratory parameters for diagnosis of toxocariasis in humans.
Keywords: Human toxocariasis, eosinophils, total IgE levels, anti-Toxocara spp. IgG.